PENERAPAN PEMBIAYAAN MUDHARABAH DALAM MENINGKATKAN PENDAPATAN NASABAH BMT AMANAH SULTRA CABANG KENDARI - Muhammad Anas Suhanri; Abdul Azis Muthalib; Nuddin Nuddin (Universitas Halu Oleo, 2018)
This study aims to determine the application of mudharabah financing at BMT Amanah Southeast Sulawesi Kendari Branch. and find out the influence of easy financing on the cost of income of BMT Amanah Sultara Kendari Branch.The sampling technique used is snowball sampling so that the number of informants in this study is five people consisting of one person from BMT Amanah Sultra and four people from the customer. In this study qualitative descriptive analysis method was used. The results showed that the first, the application of mudharabah financing at the Amanah Southeast Sulawesi BMT was in accordance with the principles of sharia and mudaraba concept, because in the revenue sharing between customers and BMT that was done by BMT Amanah there was no compulsion in sharing this result that is only according to nasbah sajah sincerity and in it, there is also no element of riba and Gharar or lack of clarity about the nasbah effort that has been carried out.